Analisis Kadar Asam Sianida dalam Solanum melongena L dan Solanum quitoense L Sebelum dan Sesudah Perebusan - Sabaniah Indjar Gama; Alimuddin Alimuddin; Eva Marliana (Faculty of Pharmacy, Universitas Mulawarman, Samarinda, Indonesia, 75117, Gedung Administrasi Fakultas Farmasi Jl. Penajam, Kampus UNMUL Gunung Kelua, Samarinda, Indonesia, 2010)
ABSTRACT Analysis cyanide acid in Solanum melongena and Solanum quitoense L before and after boiling. Cyanide acid is esthabushed by argonometricm method (Volhard) with three times repetition, for each kinds of eggplants Solanum melongena L dan Solanum quitoense L. The research showed have endireated that before boiling the content of cyanide acid Solanum melongena L (Craigi eggplant 71,712 mg/kg, kopek eggplant 46,310 mg/kg, gelatik eggplant 0 mg/kg) and Solanum quitoense L (asam eggplant 30,434 mg/kg) after boiling, the cyanide acid to slop Solanum melongena (Craigi eggplant 19,321 mg/kg, kopek eggplant 6.620 mg/kg, gelatik eggplant 0 mg/kg and Solanum quitoense L (asam eggplant 3.445 mg/kg). There is significant content have been reduced of cyanide acid in Solanum melongena L dan Solanum quitoense L Keywords: Solanum melongena dan Solanum quitoense L, Cyanide acid ABSTRAK Telah dilakukan analisis asam sianida dalam Solanum melongena dan Solanum quitoense L sebelum dan sesudah perebusan menggunakan metode Volhard dengan tiga kali pengulangan. Data hasil penelitian menunjukkan kandungan asam sianida sebelum perebusan Solanum melongena (terong Craigi 71,712 mg/kg, terong kopek 46,310 mg/kg, terong gelatik 0 mg/kg) dan Solanum quitoense L (terong asam 30,434 mg/kg) sedangkan setelah dilakukan perebusan (terong Craigi 19,321 mg/kg, terong kopek 6.620 mg/kg, terong gelatik 0 mg/kg) and Solanum quitoense L (terong asam 3.445 mg/kg). Terdapat perbedaan kandungan penting yang dapat mengurangi kadar asam sianida dalam Solanum melongena L dan Solanum quitoense L. Kata kunci: Solanum melongena dan Solanum quitoense L, Asam Sianida